Framework of property rating practice for financing neighborhoods facilities provision in Bauchi Metropolis Nigeria - Mallam Baba, Habu; Kasim, Rozilah; Mohd Diah, Mohd Lizam Bin; Martin, David; Usman Alhaji, Muktar (Science Arena Publications, 2018)
The deplorable condition of neighbourhood facilities in Bauchi metropolis persists, while the initiative aimed at raising local revenue to maintain and redevelop the local facilities has not been implemented. Property rating is one of the most stable source of local revenue, which if harnessing can finance the provision and maintenance of community infrastructures. This study has examined the existing condition of neighbourhood facilities and evaluated the most significant factors that militated against the implementation of property rating. The study has collected quantitative data, and used SPSS for reliability and exploratory factor analysis; and applied Structural Equation Modelling (SEM) with Analysis of Moment Structure (AMOS) for the analysis of the measurements and the structural models. The results showed that ‘Over-Reliance on Crude Oil Revenue’ and ‘Poor Taxation System’ are the most important factors hindering the implementation of property rating. And that the ‘Lack of Political Will’ is a factor that remarkably influenced the condition of the neighbourhood facilities in the study area. In conclusion the study has proposed Land area-based assessment for rating valuation, using Google Earth/Map for area measurement. The proposed framework was envisaged to be cost-effective in rating valuation. It was recommended that the government should diversify revenue sources from oil-based to harness all the avenues like property rating at the municipal level. Future studies should find out, apart from ‘Over Reliance on Crude Oil Revenue’ and ‘Poor Taxation System’, whether some other factors do militate against the implementation of the property rating in the study area.